2007
DOI: 10.1109/iembs.2007.4352831
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Actions of Nucleus Reuniens and the Entorhinal Cortex on EEG and Evoked Population Behavior of the Hippocampus

Abstract: Although the hippocampal theta rhythm is thought to be linked to memory processes, its mechanism of action is unknown. Furthermore, the hippocampus forms strong connections with a functionally similar structure, the medial prefrontal cortex (mPFC). The midline thalamus appears to be an intermediate between these two structures. We recorded neurons of a midline nucleus (nucleus reuniens, RE) during theta and non-theta states. Additionally, we recorded hippocampal CA1 population responses to RE stimulation. RE c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 7 publications
(13 reference statements)
3
15
0
Order By: Relevance
“…In rats, systemic ketamine dosing (an NMDA receptor antagonist, here used to mimic schizophrenia symptoms) that slowed movements, but did not produce unconsciousness, increased the spike rate of Re neurons, the power of delta (1–4 Hz) oscillations in the Re nucleus, and the modulation of Re spiking activity at delta frequencies (locally applied ketamine induced a similar electrophysiological effect; Zhang et al, 2012). It has also been reported that the spike rate of Re neurons increased during theta (4–8 Hz) oscillatory activity induced by tail pinch (Morales et al, 2007). This suggests state-dependent modulation of both spike rate and spike timing in the Re nucleus.…”
Section: Midline Nuclei Physiology and Functionmentioning
confidence: 84%
“…In rats, systemic ketamine dosing (an NMDA receptor antagonist, here used to mimic schizophrenia symptoms) that slowed movements, but did not produce unconsciousness, increased the spike rate of Re neurons, the power of delta (1–4 Hz) oscillations in the Re nucleus, and the modulation of Re spiking activity at delta frequencies (locally applied ketamine induced a similar electrophysiological effect; Zhang et al, 2012). It has also been reported that the spike rate of Re neurons increased during theta (4–8 Hz) oscillatory activity induced by tail pinch (Morales et al, 2007). This suggests state-dependent modulation of both spike rate and spike timing in the Re nucleus.…”
Section: Midline Nuclei Physiology and Functionmentioning
confidence: 84%
“…1, might provide a major influence on hippocampal CA1 neurons. The specificity of these interactions is supported by evidence that Re stimulation elicited evoked shorter-latency potentials at CA1 during theta activity (elicited by tail pinch or occurring spontaneously) compared to non-theta states, and that Re neurons showed a marked increase in rate of discharge before or after theta periods as opposed to non-theta periods (Morales et al, 2007). Interestingly, stimulation of the midline thalamus (which would include the mediodorsal thalamic nuclei to the Re in the dorsoventral axis) also results in excitatory actions on the amygdala (Zhang and Bertram, 2002)—an indirect way for information to reach the hippocampus.…”
Section: Electrophysiological Evidence For Modulation Of Cortical mentioning
confidence: 94%
“…Surprisingly few electrophysiological studies have examined RE-elicited responses in HC and mPFC (Dollemanvan der Weel et al 1997Bertram and Zhang 1999;Zhang and Bertram 2002;Viana Di Prisco and Vertes 2006;Morales et al 2007;Eleore et al 2011;Cruikshank et al 2012). In HC, Dolleman-van der Weel et al (1997) used anesthetized rats to demonstrate that RE modulates the excitability of CA1 neurons through direct excitatory and indirect inhibitory mechanisms.…”
Section: Physiology Of Re Connectionsmentioning
confidence: 99%